Gas containing intraspinal synovial cyst in the lumbar spine: Case report and literature review. (February 2020) - Sugishima, Shintaro; Kino, Keiichiro; Fujishiro, Takashi; Yano, Toma; Nakano, Atsushi; Nakaya, Yoshiharu; Hayama, Sachio; Neo, Masashi
Highlights: Gas-containing intraspinal synovial cyst is a rare clinical entity. We report such a case that was successfully treated with the surgical management. A review of literature reporting gas-containing synovial cysts was performed. Surgery should be considered promptly when nonsurgical management is not effective. Abstract: Intraspinal synovial cyst (ISC) is a well-documented pathology. It is sometimes found in the degenerative lumbar spine and can result in neurological disorders. ISC typically contains xanthochromic fluid, blood, inflammatory tissue, and/or osseous structures, enclosed by fibrous tissue. Regarding the treatment modalities, the effectiveness of both nonsurgical management, such as oral analgesics, needle aspiration, and intra-articular injection of corticosteroid drugs, and surgical management, have been reported. Previous studies have described that the ISC can contain gas, which is derived from the vacuum phenomenon of an adjacent facet joint; however, this clinical condition has never been systematically investigated because of its rarity. In the present report, we describe the case of a 68-year-old male with gas-containing ISC in the lumbar spine who was successfully treated with surgical management; additionally, we performed a literature review to discuss the decision-making process for cases of gas-containing ISC. Based on our findings and previous literature, we recommend that considering the peculiarity of the content of such lesions in addition to the ball-valve effect of a synovial cyst, prompt transition to surgical management would be pertinent when nonsurgical treatment cannot achieve satisfactory outcomes in such cases.